Adam, Satan, and the King of Tyre : the interpretation of Ezekiel 28:11-19 in late antiquity - Patmore, Hector M. (Jewish and Christian Perspectives Series, 2012)
The oracle against the King of Tyre, found in Ezekiel 28.12-19, is a difficult text that inspired diverse interpretations in Late Antiquity. For example, according to one rabbinic tradition the text spoke of the first man, Adam, while the Church Fathers found in the same text a description of the fall of Satan. This book studies the rabbinic sources, patristic literature, the Targum, and the ancient translations, and seeks to understand the reasons for the diverse interpretation, the interaction between the exegetical traditions and the communities of interpreters, in particular between Jews and Christians, and the effect the specific form and wording of the text had on the formation and development of each interpretation.